Existence of Solutions for Fractional Boundary Value Problems with a Quadratic Growth of Fractional Derivative. (13th May 2020) - Li, Yaning; Zhang, Quanguo; Sun, Baoyan
Abstract : In this paper, we deal with two fractional boundary value problems which have linear growth and quadratic growth about the fractional derivative in the nonlinearity term. By using variational methods coupled with the iterative methods, we obtain the existence results of solutions. To the best of the authors' knowledge, there are no results on the solutions to the fractional boundary problem which have quadratic growth about the fractional derivative in the nonlinearity term.